The Experimentally Studying of Solid Desiccant Wheel Performance Combined with the System of Air Conditioning (Journal of University of Babylon for Engineering Sciences, 2019)
The aim of this study was to study the performance of the system of solid desiccant dehumidification to decrease the latent load on cooling coil for the system of air-conditioning and advance the thermal comfort, thus reduce the energy consumption. Rotary desiccant wheel contains a silica gel as a solid moisture absorbent material has been utilized in this study. The wheel was a diameter of 55 cm and a thickness of 20 cm. The wheel cross sectional area is divided into two parts in aspect ratio. The large part represent dehumidification or absorption process, in this section moisture is removed from the humid air by the silica gel. While the other part represent desorption or regeneration process in this section moisture was absorbed from the humid air by the gel of silica in the first process will be removed from it. The experimental results demonstrates that the utilizing of the desiccant wheel will reduce significantly the thermal load on the cooling coil by reducing the latent load of the passing of humid air respectively via the wheel and the cooling coil